Cultural Responses to Covid-19 Pandemic: Religions, Illness Perception, and Perceived Stress - Ting, Rachel Sing-Kiat; Aw Yong, Yue-Yun; Tan, Min-Min; Yap, Chee-Khong (Frontiers in Psychology, 2021)
Many psychological researchers have proven the deteriorating effects of the COVID-19 pandemic on public mental health. In Malaysia, various COVID-19 clusters were associated with religious gatherings. From a cultural psychology perspective, how ethno-religious groups respond to this crisis originates from their unique rationality and ecological systems. Therefore, this study aimed to explore the illness perceptions of major religious groups (Christian, Muslim, Buddhist) in Malaysia towards the COVID-19 pandemic, their stress levels, and the relationship between illness perception, stress, and forms of religious expression during the lockdown period. Through an online survey method, 608 Malaysian religious believers were included in this mixed-method empirical study which adapted standardized instruments (DUREL, BIPQ, and PSS). Statistical analysis showed that all three groups reported moderate levels of stress in average without significant difference after controlling for age. Both internal and external forms of religious expression had a significant negative relationship with stress levels. Personal control, Comprehension and Emotions domains of illness perception accounted for the significant variance in the stress level. Furthermore, religious expression significantly moderated the relationship between some illness perception domains and stress. Qualitative coding revealed that most participants perceived human behaviour and attitudes, socio-political, and sociological factors as causal factors to the current pandemic. These findings confirmed the relationship between religious expression, illness belief, and stress regulation during pandemic lockdown. Incidental findings that age as a potential protective factor for Malaysian believers warrants further study. Implications for public health policymakers and religious communities on pandemic prevention and well-being promotion were discussed at the end.